A Modular Vaccine Platform Combining Self‐Assembled Peptide Cages and Immunogenic Peptides. (11th January 2019) - Morris, Caroline; Glennie, Sarah J.; Lam, Hon S.; Baum, Holly E.; Kandage, Dhinushi; Williams, Neil A.; Morgan, David J.; Woolfson, Derek N.; Davidson, Andrew D.
Abstract: Subunit vaccines use delivery platforms to present minimal antigenic components for immunization. The benefits of such systems include multivalency, self‐adjuvanting properties, and more specific immune responses. Previously, the design, synthesis, and characterization of self‐assembling peptide cages (SAGEs) have been reported. In these, de novo peptides are combined to make hubs that assemble into nanoparticles when mixed in aqueous solution. Here it is shown that SAGEs are nontoxic particles with potential as accessible synthetic peptide scaffolds for the delivery of immunogenic components. To this end, SAGEs functionalized with the model antigenic peptides tetanus toxoid632‐651 and ovalbumin323‐339 drive antigen‐specific responses both in vitro and in vivo, eliciting both CD4 + T cell and B cell responses. Additionally, SAGEs functionalized with the antigenic peptide hemagglutinin518‐526 from the influenza virus are also able to drive a CD8 + T cell response in vivo. This work demonstrates the potential of SAGEs to act as a modular scaffold for antigen delivery, capable of inducing and boosting specific and tailored immune responses. Abstract : Peptide nanoparticles demonstrate potential as synthetic vaccine delivery platforms when functionalized with immunogenic components. Self‐assembling peptide cages (SAGEs) can be functionalized with model antigenic peptides, and drive antigen‐specific responses both in vitro and in vivo. SAGEs are stable to added immunogenic modifications and, combined with their modularity, offer potential as novel scaffolds for subunit vaccines.